British Politics : A Very Short Introduction - Wright, Tony (New York Oxford University Press, 2003)
Tony Wright's 'Very Short Introduction' is an interpretative essay on the British political system, rather than merely an abbreviated textbook on how it currently works. He identifies key characteristics and shaping ideas of the British tradition, and investigates what makes British politics distinctive.
Include Index
Keywords: Great Britain -- Politics and government -- Politics, Practical